SPATIAL CONCEPT OF HOUSING ENVIRONMENT BASED-ON SABB PRINCIPLE AS INDIGENOUS KNOWLEDGE ON COVID-19 DISASTER MITIGATION IN MANDAILING NATAL - Nuraini, Cut; Alamsyah, Bhakti; Negoro, Satria Abdi (Proceeding International Conference Keputeraan Prof. H. Kadirun Yahya; Vol 1 No 1 (2022): 1st International Conference Keputeraan Prof. Kadirun Yahya, 2022)
This study aims to develop an adaptive and responsive residential spatial planning concept based on Space Attachment of Bincar-Bonom (SABB). This qualitative research employs a mixedmethod that combines case studies, literature reviews, and brainstorming with deductive analysis based on prior research findings. The study's findings indicated that the COVID-19 pandemic's adaptive and responsive residential architecture could be observed in two SABB-based ideas, such as: 1) the notion of pangolat (border) and 2) the concept of inganan (place). The term pangolat (border) refers to two distinct components of COVID-19 prevention and control : social and physical distance. The notion of inganan (place) refers to the many locations where men and women can engage in everyday activities as part of the social protection system responsive to the COVID-19 pandemic.